Efficacy and Complications of Modified Laser Iridotomy in Primary Angle Closure Glaucoma - Khanzada, Khalid Iqbal Talpur, Azfar Ahmed Mirza, Noor Bakht Nizamani, Mahtab Alam (Pakistan Journal of Ophthalmology, 2016)
Purpose: To evaluate the efficacy and immediate complications of modified laser iridotomy in primary angle-closure glaucoma. Study Design: Case series. Place & Duration of Study: Department of Ophthalmology, Liaquat University of Medical & Health Sciences, Hyderabad, Pakistan from November 2011 to May 2012. Material and Methods: In this study 115 Patients of 41 to 60 years, with diagnosis of primary angle closure glaucoma were included, while patients with secondary angle closure glaucoma and all those patients in whom angle was not visible due to corneal opacity or haze were excluded from the study. Prior to laser therapy all patients were explained about the procedure and a written consent was obtained. A combination of Argon and YAG for laser iridotomy (modified laser iridotomy) was used in all the patients. The patients were followed-up at 1stday, 1stweek, and 4 weeks after treatment with slit lamp examination and intraocular pressure measurement. The data was entered and analyzed using SPSS version 16.0.